Emergence of self-organised oscillatory domains in fungal mycelia - Tlalka, M; Bebber, D; Darrah, P; Watkinson, S; Fricker, M (Elsevier, 2007)
Fungi play a central role in the nutrient cycle of boreal and temperate forests. In these biomes, the saprotrophic wood-decay fungi are the only organisms that can completely decompose woody plant litter. In particular, cord-forming basidiomycete fungi form extensive mycelial networks that scavenge scarce mineral nutrients and translocate them over long distances to exploit new food resources. Despite the importance of resource allocation, there is limited information on nutrient dynamics in these networks, particularly for nitrogen, as there is no suitable radioisotope available. We have mapped N-translocation using photon-counting scintillation imaging of the non-metabolosed amino acid analogue, 14C-aminoisobutyrate. We describe a number of novel phenomena, including rapid, preferential N-resource allocation to C-rich sinks, induction of simultaneous bi-directional N-transport, abrupt switching between different pre-existing transport routes, and emergence of locally synchronised, oscillatory phase domains. It is possible that such self-organised oscillatory behaviour is a mechanism to achieve global co-ordination in the mycelium.